Identifying Key Competencies for Extension Communication: A Delphi Analysis to Guide Program Development - Catherine Sanders; Kevan W. Lamm; Elisabeth Ramsey (Journal of Applied Communications, 2024)
Developing communication capacities for extension professionals is key to effectively delivering relevant and impactful knowledge. Communication is used throughout extension; however, extension professionals often feel they have limited communication skills and struggle with integrating communication into their practice. The current study identified the communication competency needs of the North Carolina Cooperative Extension organization to inform professional development and training for state extension professionals. Using a three-round Delphi technique, North Carolina extension administrators and communications staff were surveyed for their perceptions of the key communication competencies needed for extension professionals. Key competencies identified by North Carolina extension professionals were categorized as interpersonal communication, cultural competence, and science communication, identified from 171 initial responses. Findings indicate that extension experts placed a high priority on engaging in science communication and the ability to translate science to the public, as well as being culturally competent. Thus, future professional development for extension professionals should focus on developing science communication strategies and fostering interpersonal and intercultural relationship building to support extension’s role in a changing agricultural food system.
Keywords: Cooperative Extension; Delphi technique; science communication; interpersonal communication; intercultural competence